FROM METRICS TO IMPACT: EXPLORING SOCIAL DIMENSION IMPACT WITHIN EMPLOYEE LENS IN BANKING SECTOR - Sianturi, Meiwinda Mariana; Hermawan, Marko S (Jurnal Akuntansi dan Keuangan Indonesia, 2026)
Background: This study explores the integration of the social dimension of Environmental, Social, and Governance (ESG) principles within the banking sector, using the GRI 400 standards as a guiding framework. Method: Drawing on qualitative data from 18 employees at different levels ranging from outsourcing staff to Group Head level at one of Indonesian private bank. Findings: The findings reveal a clear gap between formal ESG metrics and employees’ real-life experiences. Employee awareness and perceptions differ notably by position, with higher level employees often showing greater responsiveness and a stronger intention to integrate sustainability into their daily work. Conversely, outsourced and lower-level employees tend to have fewer opportunities to join social programs, access training, or engage in policy discussions—limiting both their growth and their willingness to participate in ESG initiatives. Despite growing regulatory pressure that reflects coercive isomorphism, social ESG initiatives often remain symbolic, limited to surface-level key performance indicators (KPIs) rather than being internalized as impactful values. Many employees—particularly those in outsourced or low level roles are excluded from meaningful social activities, training, and policy engagement. However, pockets of genuine progress emerge where inclusive leadership and open communication enable bottom-up participation. Conclusion: By shifting the focus from metric to impact, it calls for more participatory, employee-centered ESG strategies that foster cultural transformation and sustainability from within. Novelty/Originality of this article: This study offers a fresh perspective by exploring the social dimension of ESG through the experiences of employees, using the GRI 400 framework as a guide. It shows that ESG practices are not experienced equally across different levels of the organization. By moving beyond traditional metric-based assessments, the study uncovers a gap between what is formally reported in ESG disclosures and what employees actually experience in their daily work. In doing so, it highlights how ESG implementation in banking institutions often remains symbolic rather than truly embedded in organizational practices.